Peranan Orangtua dalam Meningkatkan Kecerdasan Spiritual Anak - Yush Nawwir; Ariesthina Laelah (Journal of Gurutta Education, 2024)
Spiritual intelligence plays a crucial role in human life. To enhance spiritual intelligence, the role of parents is pivotal as they are the first ones recognized by their children. Parents serve as the primary institution in shaping a child's character. This research aims to: 1) describe the spiritual intelligence of children in Dusun Talinga, 2) understand the role of parents in enhancing the spiritual intelligence of children in Dusun Talinga, Rante Mario Village, 3) analyze the factors that hinder and support the role of parents in improving the spiritual intelligence of children in Dusun Talinga. This research adopts a qualitative approach with an interpretative methodology, using case studies as the research method. The primary data source is parents in Dusun Talinga, with data collection techniques including interviews, observations, and documentation. Data analysis involves data reduction, data presentation, conclusion drawing, and data validity testing through triangulation and member checks. The results of the study indicate that: 1) the depiction of children's spiritual intelligence in Dusun Talinga is still imperfect due to parents' lack of awareness of their children's religious upbringing and their incomplete responsibility towards it, 2) the role of parents in enhancing children's spiritual intelligence in Dusun Talinga is evident in their guidance of children's morality, 3) inhibiting and supporting factors include children's ease of learning when taught, parents' knowledge, parents' busy schedules, limited knowledge, and difficulties in controlling children when playing outside the home.